2009
DOI: 10.1051/0004-6361/200810306
|View full text |Cite
|
Sign up to set email alerts
|

An efficient phase-shifting scheme for bolometric additive interferometry

Abstract: Context. Most upcoming CMB polarization experiments will use direct imaging to search for primordial gravitational waves through the B-modes. Bolometric interferometry is an appealing alternative to direct imaging that combines the advantages of interferometry in terms of systematic effects handling and those of bolometric detectors in terms of sensitivity. Aims. We calculate the signal from a bolometric interferometer in order to investigate its sensitivity to the Stokes parameters paying particular attention… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 25 publications
1
23
0
3
Order By: Relevance
“…In this perspective, redundancy turns out to be the crucial property to fulfill these two objectives, as shown in Charlassier et al (2009) and in the present article.…”
Section: Resultsmentioning
confidence: 53%
“…In this perspective, redundancy turns out to be the crucial property to fulfill these two objectives, as shown in Charlassier et al (2009) and in the present article.…”
Section: Resultsmentioning
confidence: 53%
“…The coefficients of the linear combination of visibilities arriving at each bolometer are just related to the phase-differences between different channels imposed by the optical combiner. This was explored in detail in (Charlassier et al, 2009) where we have shown that the visibility reconstruction can be done in an optimal way. Working with the visibilities, although it may seem logical as we are dealing with an interferometer, may not be the best approach however.…”
Section: Synthetic Imagementioning
confidence: 99%
“…4) defined by each possible pair of horns. Such a redundancy was shown to be crucial to ensure an optimal sensitivity of the bolometric interferometer (Charlassier et al, 2009) allowing for what we have called a "coherent summation of equivalent baselines". This means that all equivalent (or redundant) baselines need to experience the same phase difference configuration on the focal plane in order to maximize the signal to noise ratio of the visibilities, or of the synthetic images.…”
Section: Synthesized Beammentioning
confidence: 99%
See 1 more Smart Citation
“…In (Charlassier et al 2009), hereafter (C09), we introduced a simple formalism for the general design of a bolometric interferometer operating at a monochromatic frequency and showed that its phase shifting scheme must respect a property which we called "coherent summation of equivalent baselines". This scheme was optimized further in (Hyland et al 2009).…”
Section: Introductionmentioning
confidence: 99%